New Decade, Same Concerns: A Systematic Review of Agricultural Literacy of School Students - Amy Cosby; Jaime Manning; Deborah Power; Bobby Harreveld (MDPI AG, 2022)
In this new decade of the twenty-first century, research reports the same concerns about agricultural literacy in primary and high school students globally. A systematic review of agricultural literacy studies published between 2000 and 2020 which assess the agricultural literacy of the target population; evaluated an agricultural education program or curriculum; or developed instruments to measure agricultural literacy was conducted. The review method followed an internationally recognized protocol for selecting, screening, analyzing, and reporting outcomes. Results found that definitions of agricultural literacy have evolved from an awareness to a measure of a deeper understanding developed throughout the years of formal schooling by both formal and informal education and experiences. Informal agricultural knowledge may be gained through numerous sources and misconceptions are apparent even among those with informal familial knowledge networks. Developing agricultural literacy in school-aged children through formal education is critical. Recommendations offer innovative ways of developing agriculturally literate young people that can be used to design, deliver and evaluate programs which aim to increase the agricultural literacy of primary and secondary students across the globe.